STRATEGI PEMASARAN KERIPIK TEMPE DI KECAMATAN PEDAN KABUPATEN KLATEN - Hasnah, Hanan Nur; Kusnandar, Kusnandar; Setyowati, Setyowati (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2020)
This study aims to determine the strategic plan implemented in the marketing of tempe chips at UMKM in Pedan District, Klaten Regency, and determine the priorities of the marketing strategy of tempe chips at UMKM in Pedan District, Klaten Regency. The basic method used in this research is descriptive, analytic and SWOT-AHP integration methods. Key informants in this study include the owner of UMKM tempeh chips; production; consumer; competitor; marketing intermediary; Pedan District government; and the Klaten UMKM national departmen. The results of this study indicate that the internal factor that is the main strength is the quality of awake tempe chips, while the main weakness of the marketing of tempe chips at UMKM in Pedan District, Klaten Regency is the lack of product innovation. The external factor that becomes the main opportunity of marketing tempe chips at UMKM in Pedan District, Klaten Regency is the demand for tempe chips from consumers is high, while the main threat to market tempe chips is that competitors are more more varied in producing tempe chips products . The priority strategy that can be applied in the marketing of tempe chips is to maintain the price of tempe chips to keep regular customers.